Outcome of Proximal Femoral Nail Antirotation II fixation of Peritrochanteric Fracture of Femur - Baral, Pramod; Chaudhary, Pashupati; Shah, Amit Bikram; Banjade, Deepak; Jha, Subash Chandra (Journal of Nepal Health Research Council, 2020)
Background: Intramedullary fixation is biomechanically superior to extramedullary fixation for fracture of peritrochanteric region of femur in elderly which is often complicated due to associated osteoporosis. Helical blade of proximal femoral nail antirotation II has stronger purchase in the head of femur preventing rotation and cutout. This study was done to evaluate the outcome of Proximal Femoral Nail Antirotation II fixation in B.P. Koirala Institute of Health Sciences. Methods: Retrospective review of the data of 100 traumatic peritrochanteric fracture cases operated between March 2017 and March 2018 was done for study. Cases lost to follow-up, deaths and incomplete functional outcome (VAS, HHS), intraoperative and postoperative data were excluded. Total of 71 cases were included in the study. Results: Mean age of patients was 65 (+14) (range:19 to 86) years and were operated for intertrochanteric (54), subtrochanteric (16) and neck of femur (1) fractures. Trivial fall on ground was the commonest mechanism of injury (43 of 71). Mean injury to surgery time was 7 (+7) days and mean duration of hospital stay was 5.92 (+4) days. Mean blood loss during surgery was 132.61 (+21) ml and mean surgical time was 56 (+8) minutes. Mean visual analogue scale (VAS) Score was 7 at 2 weeks, 3 at 6 weeks and 1 at 12 weeks. Mean harris hip score was 80 (+10) at 6 months. Conclusions: Proximal femoral nail antirotation II is a reliable implant system to use for fixation of proximal femoral fractures with a good functional outcome and low complication rates. Keywords: Harris hip Score; helical blade; intramedullary fixation; peritrochanteric fracture; proximal femoral nail antirotation